A case of renal schwannoma - Kazuki Kokura; Jun Watanabe; Takaaki Takuma; Shoko Uketa; Yuichi Uemura; Masayuki Uegaki (Urology Case Reports, 2022)
The patient was referred to our department from neurosurgery for close examination of a renal mass that had been present in the lower pole of the kidney for approximately 2 year. Retrograde Pyelography and Ureteroscopy showed no obvious neoplastic lesion in the renal pelvis. Therefore, Percutaneous renal tumor biopsy was performed. The pathological result was Schwannoma. The patient was followed up for 1 year after the biopsy. No progression was observed for approximately 3 years after the renal mass was first discovered. Because renal schwannomas are extremely rare, we report this case with a literature review.